PENGEMBANGAN MEDIA INTERAKTIF BERBASIS ANDROID BERMUATAN KEARIFAN LOKAL PADA MATERI PENGENALAN ALAT MUSIK DAERAH UNTUK SEKOLAH DASAR PURWOREJO: PENGEMBANGAN MEDIA INTERAKTIF BERBASIS ANDROID BERMUATAN KEARIFAN LOKAL PADA MATERI PENGENALAN ALAT MUSIK DAERAH UNTUK SEKOLAH DASAR PURWOREJO - Muflikhul Khaq; Prasita Puspita Sari; Rintis Rizkia Pangestika (Cerdas Proklamator, 2023)
This study aims to determine the feasibility and produce a product in the form of android-based interactive media containing lokal wisdom in the introduction to regional musical instruments for elementary schools using the RnD (research and development) method. While in the development stage using the ADDIE model (analysis, design, development, implementation, evaluation). The subjects used in this study were two lecturers from the Muhammadiyah University of Purworejo as validators of media experts and material experts. Data collection techniques using interviews, questionnaires, observation, and documentation. The instrument in this study is the validation sheet of media and material experts. Data analysis uses a Likert scale to determine the quality of the Android-based interactive media product containing lokal wisdom that was developed. The results of the feasibility of android-based interactive media containing lokal wisdom from media experts get a score of 4.48 and material experts get a score of 4.54. Based on the results of data analysis, it can be concluded that the development of android-based interactive media containing lokal wisdom has the "very good" criteria. Then, it can be suitable for use in elementary schools Purworejo.